CELLULOSE BASED PCC FILLED BY METAL ORGANIC FRAMEWORK EFFICIENT HETEROGENEOUS CATALYST FOR COMPOSITE MATERIALS - B. Deepan Kumar, Dr. M. Balaraju, Dr. J. Sai Chandra, Dr. Saraswathy Nagendran, Dr. K.A. Emmanuel, K.V.L.N Murthy, (Chelonian Research Foundation, 2023)
MOF composites Precipitation calcium carbonate (PCC) packed were used to create metal-organic framework components. Inter-fiber connections are reduced in the cellulose, allowing the production of MOF. The resulting cellulose compounds have zeolite-like properties and more specific areas. The composite materials are analyzed using SEM, and co2 absorption studies. The results have sustained idea that produced cellulose paper MOF synthetic fibers get a lot of gas adsorption potential (N2, CH4, H2, CO2, etc.). Cellulose is a frequently examined and common chemical. We look at how cellular platforms have aided the formation of various MOFs and provide some insight into the wide range of uses for these new materials, including pesticide removal, pollution capture, antimicrobial surfaces, dangerous chemical degradation, and selective gas adsorption. KEYWORDS: Metal Organic Frameworks, cellulose, SEM, precipitated calcium carbonate (PCC).